Two-dimensional WSe2 flakes under high power optical excitation - Kirill Brekhov (Pensoft Publishers, 2021)
Quasi-2D layers of transition metal dichalcogenides are promising candidates for creating saturable absorbers for pulsed lasers. However, the peculiarities of intense electromagnetic radiation’s influence on such structures have not been thoroughly studied. This paper explores the dynamics of photoexcited carriers in WSe2 flakes through experimental studies. These studies found that WSe2 flakes significantly change their optical properties under the influence of a high-power optical pump, allowed estimating the thermalization time of these structures (about 2 ps), and found that full relaxation takes more than 10 ps. The concentration of carriers in the semiconductor surface layer was estimated to be about 1028 m–3. It was found that standard description models of the optical response based on exciton resonances and absorption by free carriers could not adequately describe the experiments’ results. Thus, for an accurate description of the optical response, it was necessary to consider the effects associated with Coulomb screening that are caused by the high concentration of photo-excited carriers of the optical pumping densities used in this experiment.